TECHNOLOGY OF EFFECTIVE USE OF HANDOUTS IN DRAWING SESSIONS - Ch. T. Shakirova (Web of Journals Publishing, 2024)
This article provides ideas on the development of a person who meets the modern requirements of scientific and technical progress, and on the upbringing of graphic literacy and creativity in them. It discusses the ways of effective use of handouts in the formation of basic graphic knowledge and skills in students when teaching drawing in schools and higher educational institutions, and the requirements for them.
Keywords: Competent, creative approach, handout, test, diagram, drawing, table, presentation slide, crossword.